2012
DOI: 10.1016/j.ccr.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Adult Murine Prostate Basal and Luminal Cells Are Self-Sustained Lineages that Can Both Serve as Targets for Prostate Cancer Initiation

Abstract: Summary The prostate epithelial lineage hierarchy and the cellular origin for prostate cancer remain inadequately defined. Using a lineage tracing approach, we show that adult rodent prostate basal and luminal cells are independently self-sustained in vivo. Disrupting the tumor suppressor Pten in either lineage led to prostate cancer initiation. However, the cellular composition and onset dynamics of the resulting tumors are distinctive. Prostate luminal cells are more responsive to Pten null-induced mitogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
436
7
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(486 citation statements)
references
References 47 publications
41
436
7
2
Order By: Relevance
“…Whether this is the case in humans and whether there are roles for HH in the progression of bladder carcinoma remains to be determined, especially given that constitutive upregulation in HH signaling has been detected in human bladder cancer cell lines (Pignot et al, 2012). There are likely to be interesting parallels between bladder and prostate cancer: in mouse models of prostate cancer, basal cells can also give rise to carcinomas, and the tumor cells also lose their basal cell characteristics (Choi et al, 2012;Wang et al, 2013). These few examples clearly demonstrate that, in the genitourinary system, base levels of HH signaling help maintain homeostasis and participate in tissue repair; however, in a disease context, the contribution of the HH signaling pathway can have detrimental and diverse consequences.…”
Section: Genitourinary Systemmentioning
confidence: 99%
“…Whether this is the case in humans and whether there are roles for HH in the progression of bladder carcinoma remains to be determined, especially given that constitutive upregulation in HH signaling has been detected in human bladder cancer cell lines (Pignot et al, 2012). There are likely to be interesting parallels between bladder and prostate cancer: in mouse models of prostate cancer, basal cells can also give rise to carcinomas, and the tumor cells also lose their basal cell characteristics (Choi et al, 2012;Wang et al, 2013). These few examples clearly demonstrate that, in the genitourinary system, base levels of HH signaling help maintain homeostasis and participate in tissue repair; however, in a disease context, the contribution of the HH signaling pathway can have detrimental and diverse consequences.…”
Section: Genitourinary Systemmentioning
confidence: 99%
“…Towards this end, Wang et al 6 have recently shown that transformation of a luminal stem cell population (castrationresistant Nkx3.1) can result in a rapid formation of high-grade prostatic intraepithelial neoplasia (PIN) and carcinoma. Further experiments from Xin and colleagues 7 have demonstrated that specific deletion of the tumour suppressor phosphatase and tensin (Pten) homologue in luminal cells can initiate prostate cancer independently of basal cell participation, although basal cells are shown to be able to give rise to tumours as well. Therefore, additional data are required to further understand the mechanisms by which both basal and luminal cells can be the cellular origins for prostate cancer.…”
mentioning
confidence: 99%
“…In addition, with transgenic reporter mice, a population of castration-resistant Nkx3.1-expressing luminal cells has been shown to be able to generate not only luminal cells but also other prostatic epithelial lineages 6 . Furthermore, using a lineage-tracing approach, Choi et al 7 demonstrated that basal and luminal cells in adult mouse prostates are independent self-sustaining lineages during prostate regeneration. However, using the same approach, other groups reported that in addition to unipotent luminal cells, basal cells can act as multipotent stem cells during prostate development or regeneration [8][9][10] .…”
mentioning
confidence: 99%
“…As the predominant histological subtype of prostate cancer acinar-type adenocarcinoma has a luminal phenotype, any cell type capable of generating a luminal phenotype under normal conditions is a candidate for generating luminal tumours during transformation. Both basal and luminal cells have been previously demonstrated to differentiate into luminal cells and initiate murine prostate cancer [1,3,4]. The study from the Blanpain lab suggests that several progenitors are capable of differentiation into luminal cells.…”
Section: Progenitor Cells In Cancermentioning
confidence: 99%